Extracorporeal Membrane Oxygenation in Pregnant and Postpartum Women: A Systematic Review and Meta-Regression Analysis. (February 2021) - Zhang, John J. Y.; Ong, Jamie Ann-Hui; Syn, Nicholas L.; Lorusso, Roberto; Tan, Chuen Seng; MacLaren, Graeme; Ramanathan, Kollengode
Background: Although extracorporeal membrane oxygenation (ECMO) is frequently utilized as a salvage therapy for patients with cardiopulmonary failure, outcomes of its use in peripartum patients have not been clearly established. We aimed to review peer-reviewed publications on the use of ECMO in pregnant and postpartum patients, with analyses of maternal and fetal outcomes. Methods: Data were retrieved from MEDLINE, EMBASE, and Scopus databases from 1972 up to November 2017 for publications on ECMO in peripartum patients. Search terms included "ECMO, " "ECLS, ", "pregnancy, " "postpartum, " and "peripartum." Publications with 3 or more patients were reviewed for quality using the Joanna Briggs Institute checklist for prevalence studies and case series. Results: After reviewing 143 publications, 9 observational studies met our inclusion criteria. Pooled prevalence of maternal survival was 77.2% (95% confidence interval [CI]: 64.1%-88.4%). Pooled prevalence of fetal survival was 69.1% (95% CI: 44.7%-89.8%). The level of heterogeneity across studies was low for both outcomes. Meta-regression did not reveal any correlation between pregnant women with pulmonary or cardiac indications and maternal survival. Individual patient data meta-regression demonstrated higher odds of survival for patients on venovenous ECMO compared to those on venoarterial ECMO that was close to statistical significance (odds ratio = 3.016, 95% CI: 0.901-11.144; P = .081) after adjusting for pregnancy status. Conclusions: Extracorporeal membrane oxygenation can be considered as an acceptable salvage therapy for pregnant and postpartum patients with critical cardiac or pulmonary illness.